See more with C-MORE: Addressing the need of robust cardiomyocyte morphological assessment - Rhys Wardman (Elsevier, 2021)
Robust, comprehensive assessment of cardiomyocyte morphology is essential from research and clinical perspectives, but current methods predominantly rely on only limited parameters. Addressing this, Furkel et al. present, “C-MORE: A high content single cell morphology assay for cardiovascular medicine” in this issue of Cell Reports Medicine.